Physiological in vitro sacroiliac joint motion: a study on three‐dimensional posterior pelvic ring kinematics. Issue 3 (9th December 2018) - Hammer, Niels; Scholze, Mario; Kibsgård, Thomas; Klima, Stefan; Schleifenbaum, Stefan; Seidel, Thomas; Werner, Michael; Grunert, Ronny
Abstract: The sacroiliac joint (SIJ) is a well‐known source of low back and pelvic pain, of increasing interest for both conservative and surgical treatment. Alterations in the kinematics of the pelvis have been hypothesized as a major cause of SIJ‐related pain. However, definitions of both the range and the extent of physiological movement are controversial, and there are no clear baseline data for pathological alterations. The present study combined a novel biomechanical setup allowing for physiological motion of the lumbosacral transition and pelvis without restricting the SIJ movement in vitro, combined with optical image correlation. Six fresh human pelvises (81 ± 10 years, three females, three males) were tested, with bodyweight‐adapted loading applied to the fifth lumbar vertebra and both acetabula. Deformation at the lumbopelvises was determined computationally from three‐dimensional image correlation data. Sacroiliac joint motion under the loading of 100% bodyweight primarily consisted of a z ‐axis rotation (0.16°) and an inferior translation of the sacrum relative to the ilium (0.32 mm). Sacroiliac joint flexion‐extension rotations were minute (< 0.02°). Corresponding movements of the SIJ were found at the lumbosacral transition, with an anterior translation of L5 relative to the sacrum of −0.97 mm and an inferior translation of 0.11 mm, respectively. Moreover, a flexion of 1.82° was observed at the lumbosacral transition. Within the innominate bone and at the pubic symphysis, small complementary rotations were seen around a vertical axis, accounting for −0.10° and 0.11°, respectively. Other motions were minute and accompanied by large interindividual variation. The present study provides evidence of different SIJ motions than reported previously when exerted by physiological loading. Sacroiliac joint kinematics were in the sub‐degree and sub‐millimeter range, in line with previous in vivo and in vitro findings, largely limited to the sagittal rotation and an inferior translation of the sacrum relative to the ilium. This given physiological loading scenario underlines the relevance of the lumbosacral transition when considering the overall motion of the lumbopelvis, and how relatively little the other segments contribute to overall motion.